Comprehensive and Technical Overview of Android and IOS OS - Haseeb, Abdul (International Journal of Computer Sciences and Engineering, 2015)
Google’s Android and Apple ios are operating system used primarily in mobile technology, such as tablets and smart phone’s. In these past years, the entire world has witnessed the rise of these two platforms. The iOS platform developed by Apple is the world’s most advanced mobile operating system (OS), continually redefining what people can do with a mobile device. Google’s Android platform developed by Google is an optimized platform for mobile devices with a perfect combination of an application programs, middleware and operating system (OS). This research paper will be extremely helpful to have a comparative overview between these two OS’s and also sheds light on the technical specification, market analysis, development environment aspect of these two largely operating systems. And the Comparison is done on the basis of their performances, their platform and the growth in mobile world. The Salient new key Features introduced in Android and IOS are also described.